Workers' intrinsic work motivation when job demands are high: The role of need for autonomy and perceived opportunity for blended working. (July 2016) - Van Yperen, Nico W.; Wörtler, Burkhard; De Jonge, Kiki M.M.
Abstract: Work overload or work pressure may undermine workers' intrinsic motivation. In the present research, we tested the conditions under which this may (not) occur, including the perceived opportunity to blend on-site and off-site working through the effective use of computers and modern information and communication technology. Our sample consisted of 657 workers (51% female) representing a variety of industries. As hypothesized, it is not high job demands per se, but high demands in combination with a high need for autonomy and a lack of perceived opportunities for blended working that undermines intrinsic work motivation. When workers high in need for autonomy perceived opportunities for blended working, their intrinsic work motivation was not negatively affected by increasing job demands. This main finding suggests that, particularly for workers high in need for autonomy, the perceived opportunity for blended working is an effective, contemporary resource to cope with the increasing job demands typically observed in today's workplace. Theoretically, these findings contribute to the refinement and extension of influential demands-resource models and Person-Job Fit theory. Practically, our findings may show managers how to effectively keep workers intrinsically motivated and productive in their jobs when job demands are high. Highlights: We tested conditions under which high job demands may undermine work motivation. We examined the new concept of perceived opportunity for blended working. Blended working, enabled through ICTs, works when need for autonomy is high. High job demands per se do not undermine intrinsic work motivation. We emphasize the importance of fit between work context and workers' needs.